Penerapan Model Pembelajaran Montessori Dalam Meningkatkan Motivasi Belajar Dan Penguasaan Konsep Matematika Siswa Pre-Nursery Di Tk Global Sevilla Pulomas Jakarta Timur - Mansjoer, Miranti; Susianna, Nancy (Riviera Publishing, 2025)
Early childhood education is the provision of efforts to stimulate, guide, nurture, and provide learning activities that will produce children's abilities and skills. The motivation of learning and Mastery of learning concepts in Mathematics are very important to be introduced since early childhood education. Those two competencies need to be developed in Pre-Nursery Class Global Sevilla Pulomas. The research is done to analyze the Montessori Method in improving the students’ motivation in learning, and mastery of learning concepts in Mathematics. The Montessori method is used in this research. The research was conducted in Global Sevilla Pulomas with 9 students as subjects of study. Rubrics and Communication Reports are used to measure the students’ progress in their motivation of learning. The results show a significant increase of students’ grades from cycles one, two, and three. The average score of learning motivation in cycle one is 57.58, in cycle two 86.36, and in cycle three 92.42. The average score of mastery of learning concept in cycle one is 54.55 in cycle two 68.69, and in cycle three is 81.82. It can be concluded that the Montessori Method can improve learning motivation and mastery of learning concepts in Mathematics for Pre-Nursery students at Global Sevilla Pulomas.